Influence of perceived stress on professional identity among nursing students: a chain mediating role of self-control and self-directed learning ability - Zhao, Xin; Zheng, Wen-Kai; Wang, Xiu-Huan; Fang, Jiao; Chen, Wen-Jin; Li, Na; Wen, Hai-Tao; Feng, Xiu-Juan; Wang, Mei-Fang; Heng, Chun-Ni; Cao, Wei-Na (Frontiers in Medicine, 2024)
Background A positive professional identity is key for nursing students in determining career direction and predicting future engagement in the profession. Despite its complexity and susceptibility to various influences, the factors shaping nursing students' professional identity remain poorly understood. Objectives This study aims to investigate how perceived stress can directly and indirectly influence professional identity among nursing students, with self-control and self-directed learning ability as mediators. Materials and methods A cross-sectional survey was conducted from October to December 2023, collecting data from 675 nursing students across five tertiary hospitals in Xi'an, Shaanxi Province, China. The survey captured detailed data on sociodemographic characteristics, perceived stress, self-control, self-directed learning ability, and professional identity among the participants. Descriptive analysis and correlation matrices were used to analyze participant characteristics and assess bivariate correlations. The mediation model was analyzed using the PROCESS macro for SPSS. Results Perceived stress showed a direct and negative influence on professional identity among nursing students; self-control was shown to play a mediating role between perceived stress and professional identity; self-directed learning ability was shown to play a mediating role between perceived stress and professional identity; and self-control and self-directed learning ability were shown to play a chain mediating role between perceived stress and professional identity. Conclusion Self-control and self-directed learning ability have a chain mediating role in between perceived stress and professional identity among nursing students. It suggests that nursing managers and educators can improve the self-control and self-directed learning ability of nursing students to mitigate the negative impact of perceived stress on professional identity.